Micromachined nanocrystalline graphite membranes for gas separation. (November 2018) - Fishlock, S.J.; Pu, S.H.; Bhattacharya, G.; Han, Yisong; McLaughlin, J.; McBride, J.W.; Chong, H.M.H.; O'Shea, S.J.
Abstract: Carbon nanoporous membranes show promising performance for the passive separation and sieving of different gases, for example for helium and hydrogen separation. In this paper, nanocrystalline graphite (or nanographite) has been evaluated as a membrane material for molecular sieving of helium and hydrogen from larger gas constituents. Nanographite of 350 nm thickness was prepared using plasma-enhanced chemical vapour deposition onto fused silica substrates, from which membranes were microfabricated using deep wet etching. Permeability of hydrogen and helium were 1.79 × 10 −16 and 1.40 × 10 −16 mol m m −2 s −1 Pa −1 at 150 °C respectively, and measured separation was 48 for He/Ne, >135 for H2 /CO2 and >1000 for H2 /O2 . The gas separation properties of the nanographite membranes were tested in the temperature range of 25–150 °C, and the permeation measurements show nanographite to be highly selective of helium and hydrogen over all larger gas molecules, including neon. Graphical abstract: Image 1